Application and practice of industrial big data - Aijin YUAN; Binnan YUE; Xin YAN; Jian HUANG (大数据)
With the advent of the Internet of things and the era of Cyber Physical System,more data can be collected and analyzed,and industrial big data have become important driving force for industry innovation and transformation.Unlike traditional Internet big data,industrial big data are closely integrated with industrial logic.The difference between industrial big data and internet big data was compared in detail.Combined with the classical cases,the process of demand driven transformation of traditional manufacturing industry and the development path of industrial big data were expounded.The structure and working principles of industrial big data platform were introduced.At last,taking the excavator business as an example,it shows the application effect of the industrial big data platform,and that having a share in data and models will make data based application produce more value was put forward.